Predicting international medical graduate success on college certification examinations: Responding to the Thomson and Cohl judicial report on IMG selection - Schabort, Inge (College of Family Physicians of Canada, 2014)
OBJECTIVE: To determine predictors of international medical graduate (IMG) success in accordance with the priorities highlighted by the Thomson and Cohl judicial report on IMG selection. DESIGN: Retrospective assessment using regression analyses to compare the information available at the time of resident selection with those trainees’ national certification examination outcomes. SETTING: McMaster University in Hamilton, Ont. PARTICIPANTS: McMaster University IMG residents who completed the program between 2005 and 2011. MAIN OUTCOME MEASURES: Associations between IMG professional experience or demographic characteristics and examination outcomes. RESULTS: The analyses revealed that country of study and performance on the Medical Council of Canada Evaluating Examination are among the predictors of performance on the College of Family Physicians of Canada and the Royal College of Physicians and Surgeons of Canada certification examinations. Of interest, the analyses also suggest discipline-specific relationships between previous professional experience and examination success. CONCLUSION: This work presents a useful technique for further improving our understanding of the performance of IMGs on certification examinations in North America, encourages similar interinstitutional analyses, and provides a foundation for the development of tools to assist with IMG education.